Increasing Aspartoacylase in the Central Amygdala: The Common Mechanism of Gastroprotective Effects of Monoamine-Based Antidepressants Against Stress - Yao, Kaiyun; Cao, Linyu; Ding, Hongwan; Gao, Yinge; Li, Tiegang; Wang, Guibin; Zhang, Jianjun (Frontiers in Pharmacology, 2022)
Monoamine-based antidepressants can prophylacticly protect against stress-induced gastric ulcers. Although central nucleus of amygdala (CeA) has been shown to modulate the severity of stress ulcers, little is known about the molecular mechanisms underlying gastroprotective effect of this kind of drugs. Here we first used proton magnetic resonance spectroscopy (1H-MRS), a non-invasive tool to explore the change of neurometabolites of CeA of rats pretreated with duloxetine of SNRIs during 6 h of water-immersion restraint stress (WIRS). Duloxetine decreased N-Acetyl-Aspartate/Creatine ratio (NAA/Creatine) in CeA after WIRS, which was paralleled by amelioration of gastric lesions. Meanwhile, gastric ulcer index was negatively correlated with reduced NAA/Creatine. Furthermore, intra-CeA infusion of NAA aggravated WIRS-induced gastric mucosa damage, which suggested the crucial role of reduced NAA. Western blotting was performed to identify the specific enzymes responsible for the change of contents of NAA at 0.5 h/3 h /6 h after WIRS, considering the preventative gastric protection of duloxetine. NAA catabolizing enzyme aspartoacylase (ASPA) was the only enzyme downregulated by 0.5-h WIRS and upregulated by duloxetine. Moreover, overexpressing ASPA in CeA alleviated stress ulcers. Additionally, all of other three monoamine-based antidepressants, fluoxetine of SSRIs, amitriptyline of TCAs and moclobemide of MAOs increased ASPA expression in CeA. Together, these results indicate that increasing ASPA to hydrolyze NAA in CeA is a common mechanism of gastroprotective effects against stress exerted by monoamine-based antidepressants, and ASPA is a shared target more than monoamine regulation for this kind of drugs.